Health-promoting lifestyle in mothers with vaginal childbirth and cesarean section in the postpartum period - Motahareh Govahi; Fereshteh Behmanesh; Hemmat Gholinia; Shabnam Omidvar; Hajar Adib-Rad (BMC, 2024)
Abstract Background In the postpartum period, there are numerous changes in the physical and psychological dimensions of women, which reduce the quality of life of women. The aim of this study was to compare the health-promoting lifestyle of mothers with vaginal delivery and cesarean delivery in the postpartum period. Methods This cross-sectional study was conducted on 77 pregnant women who had delivered vaginal or by cesarean section at Shohadaye Behshahr Hospital and were selected based on inclusion criteria. If the women were willing to participate in the study, a demographic questionnaire was completed, and the telephone numbers of the subjects were recorded so that the Porsline health-promoting lifestyle questionnaire could be sent to them. Data were analyzed with SPSS 22 using the T test, chi-square test and Repeated Measure ANOVA. Results There was no difference in the average score of health-promoting lifestyle and its dimensions between the two groups of vaginal delivery and cesarean section at two and six weeks after delivery. However, in both groups, the total score of health-promoting lifestyle decreased significantly over time (P < 0.001). Conclusions There was no difference in health-promoting lifestyle between mothers with vaginal and mothers with cesarean delivery at two weeks and six weeks after delivery. This requires more attention from policy makers to make vaginal childbirth more convenient, and by reducing complications after vaginal childbirth, they can improve women's healthy lifestyles and, in turn, families. Also, it seems that the other variables apart from the method of delivery should be considered, and it is necessary to distinguish these variables such as routine episiotomy in order to prevent the decrease in the level of health-promoting behaviors among women during puerperium period.